Respuesta :
1/3a - 5 - (1/6a + 3) =
1/3a - 5 - 1/6a - 3 =
1/3a - 1/6a - 5 - 3 =
2/6a - 1/6a - 8 =
1/6a - 8 <===
1/3a - 5 - 1/6a - 3 =
1/3a - 1/6a - 5 - 3 =
2/6a - 1/6a - 8 =
1/6a - 8 <===
Answer:
[tex]\frac{3a+8}{3(2a+1)(3a-5)}[/tex]
Step-by-step explanation:
We want to subtract [tex]\frac{1}{6a+3}[/tex] from [tex]\frac{1}{3a-5}[/tex].
We set up the subtraction problem as follows;
[tex]\frac{1}{3a-5}-\frac{1}{6a+3}[/tex]
We collect LCM of the denominators to obtain
[tex]=\frac{6a+3-(3a-5)}{(6a+3)(3a-5)}[/tex]
Expand the bracket in the numerator to obtain;
[tex]=\frac{6a+3-3a+5}{(6a+3)(3a-5)}[/tex]
This simplifies to;
[tex]=\frac{3a+8}{3(2a+1)(3a-5)}[/tex]